The driving mechanisms for human settlement and ecological environment in the upper minjiang watershed, China - Liao, Bo; Wang, Zelin; He, Jing; Wu, Jiaxing; Su, Jiafu (Frontiers in Environmental Science, 2023)
The Chinese urbanization process is undergoing rapid development and intensification. There is, however, little awareness of spatial development in rural areas, particularly in watersheds that are relatively backward. Consequently, human settlements have been disrupted and environmental damage has been caused. The upper reaches of the Minjiang River are not yet aware of the limited space resources and environmental elements due to topography, climate, and other factors, resulting in an unbalanced development. Human settlements and ecological environments are examined in this paper in light of the adaptive development strategy of the upper reaches of the Minjiang River watershed. This paper establishes a “habitat-ecology” variable system for the purpose of adaptability research. The study identified 35 explanatory variables, including 17 in the category of human settlements and 18 in the category of ecological environment. A total of 12 relevant research sample areas have been selected, including five target sample areas and seven comparison sample areas. As a result of differential analysis and correlation research, explanatory variables with high significance were identified as characteristic variables. In addition, a driving mechanism between human settlement and ecological environment is determined using correlation analysis results, optimal subset equations, and independent effects of variables. The results show that in the “habitat-ecology” driving mechanism model: (1) In terms of human settlement, factors such as population density, proportion of construction land, and service scope of medical facilities are the most prominent; (2) In terms of ecological environment, factors such as regional proportion, per capita water area, net flow, and grassland coverage are the most prominent; (3) Based on the element configuration of the above two research subjects, the driving mechanism with human settlement as the driving force and ecological environment as the carrying capacity is obtained.